Privatisation and Institutions: A Cross Country Analysis - Bernardo Bortolotti; Domenico Siniscalco; Marcella Fantini (Center for Economic Studies and ifo Institute (CESifo), 2000)
Privatisation, i.e. the transfer of ownership and control of state-owned enterprises, is a worldwide phenomenon. Which political, economic and institutional factors are shaping this process? This paper addresses the issue presenting new evidence from a sample of 49 countries. From an empirical analysis of the period 1977-96, the decision to privatise and the choice of privatisation method appear to be influenced by the governing political majority and public sector budget constraints, while the success of privatisation in terms of revenues and stakes sold requires suitable institutions and developed capital markets.
Keywords: 330; Keywords: Privatisation; politics; budget deficit; investor protection; enforcement of law; capital markets